Pengaruh Perceived Organizational Support terhadap Innovative Work Behavior pada Guru Sekolah Luar Biasa (SLB) - Putri Amalia Rahmah; Dinda Dwarawati (Bandung Conference Series: Psychology Science, 2023)
Abstract. Innovative Work Behavior is individual behavior that aims to reach the introduction stage or try to introduce new and useful ideas, processes, products or procedures in work, groups or organizations. To display innovative work behavior, teachers need a strong perception of management and superior support or what is called perceived organizational support which consists of three dimensions, namely fairness, supervisor support, and organizational rewards and job conditions (Afsar & Kiani, 2016). This study aims to see how much influence perceived organizational support has on innovative work behavior in 224 special education school teacher. The measurement tools used are Measuring innovative work behavior which refers to the theory of De Jong & Den Hartog (2010) and SPOS (Survey Perceived Organizational Support) which refers to the theory of Eisenberger et al. (1986). The sampling technique used is cluster random sampling. The method used is a causality quantitative method with simple linear regression analysis techniques. The results of the study show that perceived organizational support has a significant effect on innovative work behavior in SLB teachers by 33.9%. Abstrak. Innovative Work Behaviour adalah perilaku individu yang bertujuan untuk mencapai tahap pengenalan atau berusaha mengenalkan ide-ide, proses, produk atau prosedur yang baru dan berguna di dalam pekerjaan, kelompok atau organisasi. Untuk menampilkan innovative work behavior, guru membutuhkan persepsi yang kuat dari manajemen dan dukungan atasan atau yang disebut perceived organizational support yang terdiri dari tiga dimensi, yaitu fairness, supervisor support, serta organizational rewards dan job conditions (Afsar & Kiani, 2016). Penelitian ini bertujuan untuk melihat seberapa besar pengaruh perceived organizational support terhadap innovative work behavior pada 224 guru sekolah luar biasa (SLB). Alat ukur yang digunakan adalah Measuring innovative work behaviour yang mengacu pada teori De Jong & Den Hartog (2010) dan SPOS (Survey Perceived Organizational Support) yang mengacu pada teori Eisenberger et al. (1986). Teknik sampling yang digunakan adalah cluster random sampling. Metode yang digunakan merupakan metode kuantitatif kausalitas dengan teknik analisis regresi linier sederhana. Hasil penelitian menunjukkan bahwa perceived organizational support berpengaruh secara signifikan terhadap innovative work behavior pada guru SLB sebesar 33.9%.